Novel biophysical determination of miRNAs related to prostate and head and neck cancers - Hudcova, Kristyna; Trnková, Libuše; Kejnovská, Iva; Vorlíčková, Michaela; Gumulec, Jaromír; Kizek, René; Masařík, Michal (European biophysics journal, 2015)
In this study we have chosen a new approach and characterized three miRNAs (miR-23a, miR-34a and miR-320a) related to prostate cancer and head and neck cancer by spectral (circular dichroic and UV-absorption spectra) and electrochemical (voltammetry at graphite and mercury electrodes) methods. The spectral and voltammetric results, reflecting different nucleotide sequences of miRNAs, were complemented by the results of DNAs(U) having the same oligonucleotide sequences as miRNAs. The effect of the substitution of ribose for deoxyribose was shown and structural diversity was confirmed. The stability of RNA and DNA(U) was studied using CD and UV-absorption spectroscopy and melting points were calculated. MiRNA-320a with the highest content of guanine provided the highest melting point. With respect to the rapid progress of miRNA electrochemical sensors, our results will be useful for the research and development of sensitive, portable and time-efficient miRNA sensors, which will be able to diagnose cancer and other diseases.
Keywords: Male; MicroRNAs; mikro RNA; Photoelectron Spectroscopy; nádory hlavy a krku; Prostatic Neoplasms; Case-Control Studies; Head and Neck Neoplasms; mužské pohlaví; Electrochemistry; Circular Dichroism; lidé; elektrochemie; ženské pohlaví; studie případů a kontrol; fotoelektronová spektroskopie; Humans; cirkulární dichroismus; nádory prostaty; Female; Biomarkers, Tumor; nádorové biomarkery